2012
DOI: 10.1002/crat.201100356
|View full text |Cite
|
Sign up to set email alerts
|

The color of langatate crystals and its relationship with composition and optical properties

Abstract: Langatate crystals grown by the Czochralski method in 〈0001〉 and 〈01$ \bar 1 $1〉 directions both without subsequent annealing (from colorless to orange crystals) and with vacuum (colorless and pale‐green crystals) and air (orange crystal) annealing have been investigated by neutron diffraction, X‐ray diffraction and optical spectroscopy. The main types of point defects were compared with absorption bands: oxygen vacancies ‐ VO•• (0.35‐0.36 µm), the vacancies in the lanthanum position ‐ VLa‴ (0.29‐0.30 µm); the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…For LGT CK, a shift of the intrinsic absorption edge to a higher wavelength of 270 nm is observed. The absorption band at 280 nm in the spectra of CK and CI6 was recorded by authors of [5] [16] and attributed to "La vacancies" VLa′′′. The weak and wide absorption band at around 330-340 nm observed in the transmission spectra of CK was attributed [5] [16] to oxygen vacancies VO •• .…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%
See 4 more Smart Citations
“…For LGT CK, a shift of the intrinsic absorption edge to a higher wavelength of 270 nm is observed. The absorption band at 280 nm in the spectra of CK and CI6 was recorded by authors of [5] [16] and attributed to "La vacancies" VLa′′′. The weak and wide absorption band at around 330-340 nm observed in the transmission spectra of CK was attributed [5] [16] to oxygen vacancies VO •• .…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%
“…LGT crystals are commonly grown by Czochralski method using an Iridium crucible [5] [6] [10] [15]. Kimura et al [15] reported that LGT crystals contain iridium ions, which are responsible to the crystal color.…”
Section: Metal Ions Impuritiesmentioning
confidence: 99%
See 3 more Smart Citations